The Role of Government in Increasing Work Productivity in Business Organizations - Purwanto, Agus (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
Industrial relations between the government and workers are very important in increasing work productivity. The government can make policies that support increased work productivity, develop infrastructure, and develop human resources. Thus, good industrial relations between the government and workers can increase work motivation, quality of life, and economic growth. The design of this study is Literature Review, Literature review studies are used to collect data or a synthesis of sources related to research topics from various sources, including journals, books, documentation, the internet and libraries. The literature study method is a series of activities related to the method of collecting library data, reading and recording, and managing writing materials. The method of searching for articles in research journal databases and searching via the internet. The database search used is Google Scholar from 2019 to 2024. For article searches, the keywords used are also included in the data collection, namely